A DESCRIPTIVE STUDY ON RASULAN IN GUNUNGKIDUL, YOGYAKARTA SPECIAL REGION - Rahayu, Nurti (Kepariwisataan: Jurnal Ilmiah, 2019)
Rasulan is one of cultural festivals which can be found in Gunungkidul, one of the regencies in Yogyakarta Special Region. This tradition is usually held annually to express people’s gratitude for all the harvests. The local residents who mostly earn their living by cultivating their lands work together to conduct this festival by performing some kinds of activities ranging from sport competition, religious, and cultural performance. This research aims to describe the origin, sequences and the values of this tradition which party explain why the local people still preserve this festivity. An exploratory descriptive qualitative research is employed to reveal. Qualitative data are collected from documentation, and library research. In addition, some interviews are conducted to indulge more information from the village leaders who knows more about the development of this festivity. The obtained results reveal the sequence of activities from beginning until the end. This tradition also brings about various value such as religious, social, cultural and economical. This study brings some theoretical contribution and implications on the potentials of this event for tourists’ attraction.Keywords : cultural festival, motivations, perceptions, Rasulan, Gunungkidul